Swiftly moving focus points and forming shapes through the scattering media - Tran, Vinh (2018)
Propagation of light through scattering media such as ground glass or biological tissue limits the quality and intensity of focusing point. Wave front shaping technique which uses spatial light modulator (SLM) devices to reshape the field profile of incoming light, is considered as one of the most effective and convenient methods. Advanced biomedical or manufacturing applications require drawing various contours or shapes quickly and precisely. However, creating each shape behind the scattering medium needs different phase profiles, which are time consuming to optimize or measure. Here, we demonstrate a technique to draw various shapes or contours behind the scattering medium by swiftly moving the focus point without any mechanical movements. Our technique relies on the existence of speckle correlation property in scattering media, also known as optical memory effect. In our procedure, we first modulate the phase-only SLM to create the focus point on the other side of scattering medium. Then, we digitally shift the preoptimized phase profile on the SLM and ramp it to tilt the beam accordingly. Now, the incoming beam with identical phase profile shines on the same scattering region at a tilted angle to regenerate the focus point at the desired position due to memory effect. Moreover, with linear combination of different field patterns, we can generate a single phase profile on SLM to produce two, three or more focus points simultaneously on the other side of a turbid medium. Our method could provide a useful tool for prominent applications such as opto-genetic excitation, minimally invasive laser surgery and other related fields.